Impact of maternal depressive symptoms on the development of infant temperament: Cascading effects during the first year of life - Rigato, S; Stets, M; Bonneville-Roussy, A; Holmboe, K (Wiley, 2020)
Maternal depression is associated with a range of child development outcomes, including difficult temperament. This longitudinal study investigated whether depressive symptoms (DS) that mothers experience after childbirth predict infant negative affect (NA), as well as potential effects of infant NA on maternal DS, across the first year of life. In the study (N = 63), questionnaires (the Beck Depression Inventory Second Edition, and the Infant Behavior Questionnaire–Revised Very Short Form) were administered at 2 weeks, 4, 6, and 9 months after birth. Using path analysis, we tested five different models that could explain the relationship between maternal DS and infant NA. The best‐fitting model showed that the days immediately following childbirth represent an important time for the development of infant temperament as maternal mood significantly predicts infant NA for at least 4 months after birth. This does not constitute a single sensitive period; a new predictive effect emerges around 4 months of age, suggesting cascading influences of maternal DS across the first 6 months of life. These results suggest a need for support, should a mother experience DS, not only immediately after birth, but also throughout the early stages of parenting.